Pengaruh Rekrutmen dan Pengembangaan Karir terhadap Kinerja Pegawai Pada Kantor DPRD Provinsi Sumatera Selatan - Selly Mariska; Hamid Halin; Meilin Veronica (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The study analyzed the impact of recruitment and career development on employee performance in the Regional House of Representatives (DPRD) Office of South Sumatera Province. A quantitative approach was used, and data were collected through the distribution of questionnaires to 76 respondents. The data were analyzed using multiple linear regression, classical assumption tests, t-test, and F-test. The research findings indicate that recruitment has a significant positive effect on employee performance, with a significance value of 0.041. Similarly, career development also has a significant positive effect on employee performance, with a significance value of 0.000. Furthermore, both recruitment and career development together have a significant positive effect on employee performance, with a significance value of 0.000. The coefficient of determination analysis reveals that the variables of recruitment and career development explain 23.4% of the variance in employee performance, while the remaining 76.6% is influenced or explained by other variables beyond the scope of this study